(untitled) (Colombia Medica, 2024)
Recent studies of intervention in sedentary subjects, or those with neurological lesions, suggest that increased motor activity (exercise/physical activity), performed at moderate intensities and habitually, could have beneficial effects on the vascular function. However, the physiological effects of interventions conducted with facilitating techniques of the motor activity, such as Kabat’s proprioceptive neuromuscular facilitation techniques (PNF) on vascular function are unknown, even though such physiological effects are proposed in said postulates. This report presents the usefulness of PNF on vascular function in three healthy volunteers. The patterns of Kabat’s PNF increase, just like the models or contractile isotonic activity proposed in this test, the tension of vascular friction, which relates to better vascular function.